Peran Teman Sebaya Dalam Upaya Meningkatkan Kepercayaan Diri Peserta Didik (ILIN Institute Makassar, 2019)
The purpose of this study was to find out how the confidence of students of class VIII Middle School 134 West Jakarta. The research method in this article uses library research. The results of this study indicate that adolescents in developing their potential need to have self-confidence. Learners need a container in an effort to express and train self-confidence. Besides guidance from parents, teachers, peers, and the environment can affect self-confidence. Development of self-confidence can be done in the school environment. One container that trains students' confidence through guidance and counseling services in group settings. Students who are members of a group will share with each other, exchange ideas, give examples or manipulate behavior.